Solvability of Some Fractional Boundary Value Problems with a Convection Term. (26th March 2019) - Wei, Yongfang; Bai, Zhanbing
Abstract : This paper is devoted to the research of some Caputo's fractional derivative boundary value problems with a convection term. By the use of some fixed-point theorems and the properties of Green function, the existence results of at least one or triple positive solutions are presented. Finally, two examples are given to illustrate the main results.